Profitability and Economic Efficiency in Gillnet Fishing in Guimaras Strait and Adjacent Waters, Western Visayas, Philippines - Subade, Rodelio Fernandez (1991)
Gillnets contribute a sign if i cant portion of fish production in the Philippine fisheries sector, as well as in Guimaras Strait and adjacent waters. It has been found out however, that many small-scale or municipal fishermen, to which the gillnet fishermen belong are living below the poverty threshold. Moreover, a number of studies and available secondary data showed the evident overfishing in Guimaras Strait and adjacent waters. This study examines the socio-economic profile, profitability and economic efficiency in gillnet fishing in Guimaras Strait and adjacent waters. The socio-economic profile revealed that most of the gillnet fishermen attained elementary or high school level of education. Average household size was 5.7 members while 71 percent of the households were dependent on only one income earner in the family. Sixty one percent of the households depended on fishing as the only source of income. The study also found that there were other employment alternatives, aside from fishing, which were available for the gillnet fishermen. Costs and earnings analysis showed that both drift gillnets and bottomset gillnets earned fishing incomes below that of the national poverty threshold. Encircling gillnets, meanwhile, earned 68675.68 pesos, the highest of the three gear types. The normalized restricted translog profit function was used to assess whether gillnet fishermen were able to maximize profits and to examine relative economic efficiency. The results which was estimated using the seemingly unrelated regressions (SUR) technique, revealed that all gillnets were not able to maximize profits based on pooled regressions and indi vidual gear type regressions. Encircling gillnets were found to be the most economic efficient while the drift gillnets were found to be the least economic efficient.The price elasticity of demand for labour was found to be inelastic (-0.79). Own price elasticity for fuel was close to unity (-0.96 ), while that for crew provisions was quite elastic (-1. 38 ). Cross price elasticity estimates revealed that the above (three) variable inputs were substitutes at varying degrees. Input demand elasticities for labour, fuel, and crew provisions with respect to net mesh size suggest that bigger net mesh size would lead to lower labour and fuel use, and lower crew provisions. The results also showed that increase in fish prices will increase labour, fuel and crew provisions use. The estimated own price elasticity of output or fish catch implied the evident overfishing in Guimaras Strait and adjacent waters. This finding confirms the assessment of previous studies and the suggestion of secondary data about the status of the fishery.